Simply tomato : 100 recipes for enjoying your favorite ingredient all year long - Holmberg, Martha (Artisan, 2023)
"Americans eat more tomatoes than any vegetable except for the potato. But what do we do with all those tomatoes? Acclaimed chef, cooking teacher, and author Martha Holmberg shares 75 recipes to turn the tomato into glorious dishes. Whether it's a fresh-off-the-vine tomato or a just-picked-from-the-supermarket-shelf tomato, Holmberg has ideas to make the best of our favorite summer fruit. There are three versions of gazpacho, five ways to top roasted tomato puff pastry, plus Tomato and Zucchini Gratin, Classic Panzanella, Tomato Risotto, and Stuffed Tomatoes with Spiced Beef Piccadillo. With more tomato varieties in existence than ever before, Holmberg explains which tomatoes work best with which recipes: choose a beefsteak to roast with fish or pick cherry tomatoes to toss with corn in a quick summer salad. Holmberg also reveals her secret, umami-packed ingredient-tomato water. She calls it a "magical elixir" that can add intense tomato flavor to most anything you make"--